PENGARUH KINERJA KEUANGAN TERHADAP PERTUMBUHAN EKONOMI, PENGANGGURAN DAN KEMISKINAN - Syamsudin Syamsudin; Bayu Tri Cahya; Syahrina Nurmala Dewi (Jurnal Manajemen Dayasaing, 2015)
The Purpose of this research is to examine directly effect variables financial performance on economic growth, to examine directly effect economic growth on jpoverty and unemployment also to examine indirectly effect variables financial performance on poverty and unemployment. The samples of study are region expense and revenue budget in 2006 – 20011 at 7 municipal. The result of study with regression indicate that variables finacial performance namely independently ratio, directly have positive significantly effect on economic growth, while effectiveness ratio and efficiency ratio directly have not significantly effect on economic growth. At economic growth directly have positive significantly effect on unemployment and also directly have positive significantly effect on poverty. To examine indirectly among variables financial performance on unemployment and povery indicate independently ratio, effectiveness ratio and efficiency ratio have significant effect on unemployment and poverty, while effectiveness have not significant effect on unemployment and poverty.